Depression in Neurologic Disorders : Diagnosis and Management. - Kanner, Andres (John Wiley & Sons, 2012)
The first part of the book begins with an overview of depression, its incidence and manifestations and neurobiological origins; how it's diagnosed; and its relevance to neurology, in particular to suicidality. The second part looks at depression in distinct conditions, in particular: migraine, stroke, epilepsy, Parkinson's Disease, Huntington's Disease, dementia, and traumatic brain injury. This useful guide takes a practical approach, with ""tips and tricks"" boxes, case studies, points of interest boxes, and take-home summaries.